GIGANTEA regulates phytochrome A-mediated photomorphogenesis independently of its role in the circadian clock - Oliveiro, Karina Andrea (2007)
GIGANTEA (GI) is a nuclear protein involved in the promotion of flowering by long days, in light input to the circadian clock, and in seedling photomorphogenesis under continuous red light but not far-red light (FR). Here, we report that in Arabidopsis ( Arabidopsis thaliana ) different alleles of gi have defects in the hypocotyl-growth and cotyledon-unfolding responses to hourly pulses of FR, a treatment perceived by phytochrome A (phyA). This phenotype is rescued by overexpression of GI. The very- low-fluence response of seed germination was also reduced in gi . Since the circadian clock modulates many light responses, we investigated whether these gi phenotypes were due to alterations in the circadian system or light signaling per se. In exper- iments where FR pulses were given to dark-incubated seeds or seedlings at different times of the day, gi showed reduced seed germination, cotyledon unfolding, and activity of a luciferase reporter fused to the promoter of a chlorophyll a/b -binding protein gene; however, rhythmic sensitivity was normal in these plants. We conclude that while GI does not affect the high- irradiance responses of phyA, it does affect phyA-mediated very-low-fluence responses via mechanisms that do not obviously involve its circadian functions